E-services and their Role in B2C E-commerce - Irissappane, D. Aravazhi (Indian Journal of Marketing, 2004)
It is only now that Governments have recognized the fact that markets should perform a crucial economic function of linking supply and demand and at the same time, provide safe guards to the producer in terms of rational market practices and safety measures facilities. Owing to globalization and de-regulation, developing countries have realized that the objectives in the 21st Century should be towards making efforts to bring the benefit of the power of the modern technology and marketing techniques to the aid of the customer with the help E-Services.